Tawaran hermeneutika untuk menafsirkan Alquran - Akbar, Ali (Wacana, Journal of the Humanities of Indonesia, 2005)
Hermeneutics is a word that becomes popular lately especially among postmodernist people. Since the definition and the scope become broader, many groups of people can use hermeneutics nowadays. One of the application of hermeneutics is the interpretation of Al-Qur'an, the Moslems' holy bible. It is known that Moslems has their own way in interpreting their bible, with Tafsir. The focus of this paper is to convey the similarity and the difference between hermeneutics and Tafsir, and also the Moslems' opinion toward the interpreter who use hermeneutics as the frame of his interpretation.